Financial analysis in Hong Kong : qualitative examination of financial statements for CEOs and board members - Kwok, Benny K. B. (Chinese University Press, 2013)
Financial statements facilitate the communication between corporations and various stakeholders. The integrity, stability, and transparency of such communication help to preserve Hong Kong as a top global financial centre. To many laypersons, looking through financial statements can be like reading novels in a foreign language, with a sea of jargon obscuring the statements' true meaning. This book offers a clear, concise reference for analysing corporations' financial statements. Based on the evaluations of published financials, this book is a convenient standalone guide for both novices and financial professionals - in the boardroom and beyond.